In situ IR Spectroscopy as a Tool to Better Understand the Growth Mechanisms of Plasma Polymers Thin Films. Issue 11 (26th May 2015) - Ligot, Sylvie; Thiry, Damien; Cormier, Pierre‐Antoine; Raynaud, Patrice; Dubois, Philippe; Snyders, Rony
Abstract : Aiming to get a better understanding of the growth mechanism during the plasma polymerization process of ethyl lactate, the surface reactivity of ester‐bearing fragments has been determined by combining in situ FTIR spectroscopy and XPS measurements. While the plasma density of the reactive ester‐bearing fragment decreases by one order of magnitude (from ∼2 × 10 20 m −3 to ∼2 × 10 19 m −3 ) as the power increases from 60 to 280 W, the ester group density in the plasma polymer films decreases from ∼1.5 × 10 19 m −2 /m2 to ∼1.7 × 10 18 m −2 . The associated incorporation efficiency of the reactive ester‐bearings fragments in the films ( σ ester ) consequently increases from 2.6 × 10 −6 to 1.3 × 10 −4 when increasing the power. This behavior is attributed to higher activation the growing film surface. Abstract : In this work, a new methodology allowing determining apparent sticking coefficients of specific fragments in plasma polymerization discharges is reported. As a case study, ethyl‐lactate has been used as a precursor for synthesizing ester‐containing plasma polymer films. By means of in situ FTIR spectroscopy and kinetic gas theory, the reactive ester‐bearing fragments flux incoming to the substrate was estimated while the density of ester groups in the plasma polymer has been probed by XPS. The comparison of these values allows calculating an incorporation efficiency for the ester‐bearing fragments.